Oleic Acid Protects Against Oxidative Stress Exacerbated by Cytarabine and Doxorubicin in Rat Brain - Calderón Guzmán, David; Osnaya Brizuela, Norma; Ortíz Herrera, Maribel; Juárez Olguín, Hugo; Hernández García, Ernestina; Valenzuela Peraza, Armando; Barragán Mejía, Gerardo (Anti-Cancer Agents in Medicinal Chemistry, 2016)
Aim: The objective of this study was to analyze the effect of doxorubicin and cytarabine on biogenic amines and oxidative biomarkers in the brain of rats treated with oleic acid. Methods: Thirty-six Wistar rats distributed in 6 groups, were treated as follows: group 1 (control), NaCl 0.9%; group 2 doxorubicin (1mg/kg); group 3 cytarabine (70mg /kg); group 4 oleic acid (1500μl/kg); group 5 doxorubicin + oleic acid; group 6 cytarabine + oleic acid. All compounds were administered intraperitoneally for 5 days. The Rats were sacrificed after receiving the last administration and their brains were dissected in cortex, hemispheres, and cerebellum/medulla oblongata. Blood samples were obtained on sacrifice to assess the levels of glucose and triglycerides. In each brain region, lipoperoxidation (TBARS), H2O2, Na+, K+ ATPase, glutathione (GSH), serotonin metabolites (5-HIAA) and dopamine were measured using validated methods. Results: Cytarabine decreased the levels of dopamine, TBARS, GSH, H2O2 and ATPase in all regions. Doxorubicin combined with oleic acid increased the levels of GSH in cortex, and decreased ATPase in cerebellum/medulla oblongata. Conclusion: These results suggest that the reduction of dopamine and oxidant effect during cytarabine treatment could result in brain injury but could be prevented by oleic acid supplementation.
Keywords: cytarabine